Law and Theological Interpretations of Sin and Punishment - Purwanto, Edi (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
This article explores the evolving concepts of sin and punishment through an interdisciplinary analysis rooted in theology and legal theory. It examines how theological traditions understand sin as a spiritual rupture and punishment as a path to restoration, while legal systems treat punishment as a rational mechanism to uphold justice and social order. The study traces the shifting boundaries between divine justice and secular law through historical and thematic analysis, revealing how moral responsibility, repentance, and mercy have been interpreted across various contexts—from ancient religious codes to Enlightenment jurisprudence. The article also analyzes contemporary ethical debates surrounding retributive and restorative punishment models. By integrating theological reflection with legal-historical insights, this study contributes to a deeper understanding of how societies conceptualize wrongdoing and justice and advocates for more holistic approaches to moral and legal accountability.